Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Motivasi Kerja Guru SMP Negeri 1 Katibung - Hasbullah Hasbullah; Trio Rubiawan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Human resources have an important role both individually and in groups in organizations and human resources are one of the main drivers of the smooth running of business activities, even the back and forth of the company is determined by the existence of its human resources. This study aims to determine the influence of leadership style and work environment on work motivation. Determination of the number of samples in this study using saturated sampling method. The sample of this study was all teachers of SMP Negeri 1 Katibung totaling 47 people. This study used primary data with a hypothesis testing method using Multiple Linear Regression. The results showed that simultaneously or partially leadership style and work environment affect work motivation.